Policing as a performing art? The contradictory nature of contemporary police performance management. (July 2018) - de Maillard, Jacques; Savage, Stephen P
Performance management in criminal justice organizations has become a prominent issue in many countries and has faced increasing criticisms by scholars and practitioners. In this regard it is important to examine empirically how performance frameworks work concretely. We do so through the empirical examination of 'performance regimes', that is, the sets of performance indicators, internal procedures, instruments and processes of internal accountability through which performance is defined, assessed and monitored work in police organizations. By using the categories of traditional (target-based, top–down and short-term) and advanced (processes, more deliberative and creative and long-term) performance regimes, we have charted a process of evolution illustrated by the experience of two police forces in England. We argue that police performance management is a contradictory and hybrid process containing elements of both traditional and advanced regimes and in constant flux between them. Problem-solving and a focus on the quality of processes coexist with cascading pressures, an emphasis on numerical targets and other features of more traditional regimes.